1984
DOI: 10.1007/bf00420929
|View full text |Cite
|
Sign up to set email alerts
|

Developmental and nutritional regulation of the messenger RNAs for fatty acid synthase, malic enzyme and albumin in the livers of embryonic and newly-hatched chicks

Abstract: The mRNAs for fatty acid synthase and malic enzyme were almost undetectable in total RNA extracted from the livers of 16-day old chick embryos. Both mRNAs increased in abundance between the 16th day of incubation and the day of hatching. In neonates, fatty acid synthase mRNA level was dependent on nutritional status, increasing slowly if the chicks were starved and rapidly if they were fed. The abundance of malic enzyme mRNA decreased in starved neonatal chicks and increased in fed ones. When neonates were fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
22
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 20 publications
7
22
0
Order By: Relevance
“…This precludes the possibility of substantial posttranslational modifications resulting from the action of the mex + product. This is consistent with observations in chicks and rats on the nutritional and hormonal regulation of ME, where the regulation appears to exert its influence at the pretranslational level (Magnuson and Nikodem, 1983;Morris et aL, 1984).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This precludes the possibility of substantial posttranslational modifications resulting from the action of the mex + product. This is consistent with observations in chicks and rats on the nutritional and hormonal regulation of ME, where the regulation appears to exert its influence at the pretranslational level (Magnuson and Nikodem, 1983;Morris et aL, 1984).…”
Section: Discussionsupporting
confidence: 90%
“…In chicks, regulation of mRNA levels throughout development and during nutritional manipulation controls the relative rates of ME synthesis with decreased abundance in starved neonatal chicks and increased in fed organisms (Morris et al, 1984). Similarly, supplementation of Drosophila melanogaster diet with lipid decreased the concentration of NADP +-dependent enzyme molecules capable of generating NADPH for lipogenesis (Geer et al, 1976).…”
Section: Discussionmentioning
confidence: 98%
“…A highly similar pattern has been described in turkey poults by Szabó et al (2005), comparing the post-hatch state to the entire rearing phase of 20 weeks. The relatively low plasma albumin level in the immediate post-hatch period is also supported by the results of Morris et al (1984), who reported a strong decrease for albumin mRNA in the chicken embryo just before hatching. The subsequent quick increase of albumin concentration (during the 1st week) and the relatively balanced globulin levels finally led to a quite steady ratio of these compounds.…”
Section: Nitrogenous Compoundssupporting
confidence: 65%
“…In the liver, the activity of FAS, like most lipogenic enzymes (95), is regulated through nutrients and hormones. Starvation causes a decrease in the activity of the enzyme, and refeeding restores it (3,67). A similar effect of refeeding is also observed on the mRNA expression level and stability, as well as on the transcription (3,41,48,52,66).…”
mentioning
confidence: 76%